Synthesis and Studies of Spectral and Thermal Properties of Some Mixed Ligand Complexes of Thorium(IV) and Dioxouranium(VI) With Semicarbazones as Primary Ligand and Sulfoxide as Secondary Ligand - Ram K. Agarwal; Surendra Prasad; N.K. Sharma (Iranian Journal of Chemistry & Chemical Engineering, 2004)
The present work describes the studies on the coordination behaviour of 4[N-(benzalidene) amino]antipyrine semicarbazone (BAAPS) (I), 4[N-(furfural)amino]antipyrine semicarbazone (FFAAPS) (II) and 4[N-(cinnamalidene)amino]antipyrine semicarbazone (CAAPS) (III) in presence of dimethyl sulfoxide (DMSO) or diphenyl sulfoxide (DPSO) towards Th4+ and UO22+ salts. All the complexes were isolated in non-aqueous solvents like ethanol or acetone. The mixed ligand complexes have the general composition ThX4(L)DPSO ( X = Cl, Br, I, NCS or NO3), Th(ClO4)4(L)2DPSO (L = BAAPS or CAAPS), UO2X2(L)DMSO (X = Br, I, NCS, NO3 or CH3COO) and UO2(ClO4)2(L)2DMSO (L=FFAAPS or CAAPS). The analytical data include elemental analyses, molecular weight determination, conductivity, spectral and thermal studies. XRD-powder diffraction of two representative thorium(IV) complexes have also been reported.In these complexes, the primary ligands behave as neutral tridentate (N, N, O) ligand, while the secondary ligand (DMSO or DPSO) acts as unidentate oxygen donor. Thorium(IV) displays coordination number 6,7,8 or 12, while uranium(VI) ion displays coordination number 8, 9 or 10 depending on the nature of anionic ligand.